A plug-and-play modular microcapillary platform for the generation of multicompartmental double emulsions using glass or fluorocarbon capillaries. Issue 14 (8th June 2021) - Farley, Sean; Ramsay, Kaitlyn; Elvira, Katherine S.
Abstract : Flexible resin junction boxes to form plug-and-play microcapillary platforms to create multicompartmental double emulsions. Abstract : Although multiple emulsions have a wide range of applications in biology, medicine, chemistry and cosmetics, the use of microfluidic devices to generate them remains limited to specialist laboratories. This is because of the expertise required to design and operate these technologies. Here we show a plug-and-play microcapillary platform for the generation of multicompartmental double emulsions which only requires a low cost 3D printer for fabrication and syringe pumps for operation. Our microcapillary platform is modular because we fabricate junction boxes from a flexible resin to hold and align any type of standard glass capillary or piece of tubing for droplet formation without the need for capillary alignment. The flexible resin enables total sealing of the capillaries without the need for gaskets or adhesives, and the ability to use any type of capillary or tubing means that surface treatment is not required. We show how our microcapillary platform is able to generate water-in-oil-in-water, oil-in-water-in-oil, and oil-in-oil-in-water multicompartmental double emulsions with between 1 and 10 inner droplets with high accuracy and reproducibility using standard oils (FC40, mineral oil) and inexpensive surfactants (sodium dodecyl sulfate, SDS or 1 H, 1 H, 2 H, 2 H -perfluoro-1-octanol, PFO). Additionally, we show the formation of binary multicompartmental double emulsions, where two types of inner phase droplets can be encapsulated in the multicompartmental emulsions. Our results demonstrate how simple and accessible tools can be employed to generate a powerful modular microcapillary platform. We anticipate that the simplicity of fabrication and operation of this platform, coupled with its ability to make a wide variety of different types of emulsions, will be attractive both to microfluidic laboratories and to those without microfluidic expertise who need an enabling tool for multicompartmental double emulsion formation.